Earth-to-air heat exchanger system : a study on the role of ground cover and system validation in Malaysian climate - Alkhalaf, Haitham (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2014)
This thesis is an investigation into the performance of Earth-to-Air Heat Exchanger (EAHE) in Malaysian climate. The passive cooling technology, where the ground is used as a heat sink to produce cooler air, is an emerging of area of interest in Malaysia. The aim of this thesis is to find the best ground cover in improving the EAHE proficiency through thermal model using computer simulation. The pipe, which was used in the thermal model, has same parameters of the real pipe which is 3 inches diameter, 50 meters in length, made of PVC, has the velocity of flow air was 1 m/s and buried in a 4-meters depth. The performance of the EAHE was simulated using loam, clay, silty clay, sandy clay loam as back fill material. It was found that sandy soil is the best cover material.